Trends in the Netherlands 2016 - Netherlands. Centraal Bureau voor de Statistiek (CBS) (The Hague: Statistics Netherlands, 2016)
Trends in Netherlands 2016 provides by describing trends in Dutch society with special focus on migration, wealth and the economy, alongside others topics.
1. Society -- 2. Economy -- 3. Labour and Income -- 4. About Statistics Netherlands
Keywords: Netherlands; Statistics; Economic conditions--Statistics; Economic history